Clay-supported copper nitrate (Claycop): a mild reagent for the selective nitration of aromatic olefins - Begari, Eeshwaraiah; Singh, Chandani; Nookaraju, U.; Kumar, Pradeep (Synlett, 2014)
A straightforward and highly selective method has been developed for the nitration of a wide variety of aromatic and aliphatic olefins by using a clay-supported copper nitrate (Claycop) and a catalytic amount of (2,2,6,6-tetramethylpiperidin-1-yl)oxyl, an inexpensive and mild reagent system. High conversions and exclusive E-selectivity, together with the environmentally benign nature of the Claycop reagent, make this a green method and an attractive alternative to established methods.
Keywords: alkenes; nitrations

Carbon-carbon bond forming reactions: application of covalently anchored 2,4,6-triallyloxy-1,3,5-triazine (TAT) Pd(II) complex over modified surface of SBA-15 to Heck, Suzuki, Sonogashira and Hiyama cross coupling reactions - Singh, Chandani; Jawade, Kiran; Sharma, Priti; Singh, Anand P.; Kumar, Pradeep (Catalysis Communications, 2015)
A highly active SBA-15-TAT-Pd(II) catalyst was synthesized from organofunctionalized SBA-15 and 2,4,6-triallyloxy-1,3,5-triazine. The catalyst was employed in carrying out Heck, ``copper-free'' Sonogashira, Suzuki and Hiyama cross coupling reactions. Under the optimized conditions the catalyst displays excellent catalytic activity in delivering the desired products in good to excellent yields. The catalytic system exhibited superior activity regarding the time taken for the completion of reaction, isolation, Pd loading (0.62 mmol%) and yields of products as compared to the earlier reported heterogeneous SBA-15 anchored Pd catalysts. The catalyst could be recycled and reused for five times without any appreciable loss of catalytic activity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heck; Hiyama; SBA-15-TAT-Pd(II) catalyst; Sonogashira; Suzuki